(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Maternal and child health (MCH) is a fundamental component of public health nursing, with far-reaching implications for the well-being of individuals and communities. This abstract delves into the multifaceted landscape of MCH, emphasizing the pivotal role of public health nurses in promoting positive outcomes for mothers and children. Through evidence-based interventions, collaboration, and advocacy, public health nurses work to address maternal and child health disparities, enhance access to care, and foster healthy behaviors. Key interventions include prenatal care, postpartum support, childhood immunizations, and community- based initiatives. This abstract highlights the importance of preventive care, cultural competence, and equity in achieving optimal MCH outcomes. By prioritizing maternal and child health and implementing comprehensive strategies, public health nurses contribute to building healthier communities and nurturing future generations.